2015
DOI: 10.3390/v7092852
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol, a Lignan Biphenol Derived from the Magnolia Tree, Inhibits Dengue Virus Type 2 Infection

Abstract: Dengue is the most widespread arbovirus infection and poses a serious health and economic issue in tropical and subtropical countries. Currently no licensed vaccine or compounds can be used to prevent or manage the severity of dengue virus (DENV) infection. Honokiol, a lignan biphenol derived from the Magnolia tree, is commonly used in Eastern medicine. Here we report that honokiol has profound antiviral activity against serotype 2 DENV (DENV-2). In addition to inhibiting the intracellular DENV-2 replicon, hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…Honokiol anticancer activity has been extensively investigated, but the study of honokiol antiviral activity remains limited. Only two reports have shown that DENV-2 and HCV infection are inhibited by honokiol with different underlying mechanisms (Lan et al 2012;Fang et al 2015). In the current study, we show that honokiol inhibits HSV-1 infection through blocking HSV-1 viral DNA replication and gene expression, the combination of honokiol with clinical antiherpesvirus drug acyclovir enhanced inhibition of HSV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honokiol anticancer activity has been extensively investigated, but the study of honokiol antiviral activity remains limited. Only two reports have shown that DENV-2 and HCV infection are inhibited by honokiol with different underlying mechanisms (Lan et al 2012;Fang et al 2015). In the current study, we show that honokiol inhibits HSV-1 infection through blocking HSV-1 viral DNA replication and gene expression, the combination of honokiol with clinical antiherpesvirus drug acyclovir enhanced inhibition of HSV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated the impact of honokiol on microbial infection. Honokiol not only inhibits various human pathogenic fungi infection (Bang et al 2000;Jin et al 2010;Jacobo-Salcedo Mdel et al 2011) and functions as an antibacterial agent (Park et al 2004;Li et al 2016;Sakaue et al 2016), also blocks hepatitis C virus (HCV) infection by targeting cell entry and viral replication (Lan et al 2012) and dengue virus type 2 infection (DENV-2) by inhibiting viral replication, gene expression and endocytotic process of DENV-2 (Fang et al 2015). However, honokiol shows weak activity against HIV-1 in human lymphocytes (Amblard et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Elsholtzia contains flavonoids and coumarins, and has the functions of heat clearing, wetting, antibacterial, anti-inflammatory and other pharmacological actions [19]. Honokiol in Magnolia officinalis also has the effect of inhibiting virus replication [20,21]. In the present study, XJXRY clearly demonstrated therapeutic effects in mice infected with influenza in a hot and humid environment, and reduced pulmonary inflammation in normal WT mice, but had no significant effect on TLR7 −/− mice.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, magnolol, the main component of Cortex Magnoliae Officinalis, has antioxidative [ 16 , 17 ], inflammation regulation [ 18 ], cancer cell inhibition [ 19 ] and other effects. At the same time, honokiol also has an anti-viral activity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%